Age and Sex Differences in Heart Failure With Preserved Ejection Fraction - Kobak, Kamil Aleksander; Zarzycka, Weronika; Chiao, Ying Ann (Frontiers in Aging, 2022)
Heart failure with preserved ejection fraction (HFpEF) is a multi-organ disorder that represents about 50% of total heart failure (HF) cases and is the most common form of HF in the elderly. Due to its increasing prevalence caused by the aging population, high mortality and morbidity, and very limited therapeutic options, HFpEF is considered as one of the greatest unmet medical needs in cardiovascular medicine. Despite its complex pathophysiology, numerous preclinical models have been established in rodents and in large animals to study HFpEF pathophysiology. Although age and sex differences are well described in HFpEF population, there are knowledge gaps in sex- and age-specific differences in established preclinical models. In this review, we summarize various strategies that have been used to develop HFpEF models and discuss the knowledge gaps in sex and age differences in HFpEF.